Impact of Grain Trade Policies on Prices and Welfare : Evidence from Malawi - Fuje, Habtamu; Pullabhotla, Hemant K. (World Bank, Washington, DC, 2020)
Restricting cross-border trade through export bans in an attempt to stabilize domestic prices has been a particularly popular policy tool used by many sub-Saharan countries in recent years. However, little is known about how the variability in harvests and seasonality -- two critical dimensions of smallholder agriculture in Africa -- mediate the effects of export bans on household welfare. This study assesses the short-term impact of export bans on prices and welfare of households in Malawi, accounting for these heterogeneities. It uses monthly panel data on maize prices from 152 markets in Malawi and neighboring countries. To identify the impacts of the bans, the study compares the change in price dispersion between a domestic market in Malawi and another market in a neighboring country, relative to the price dispersion between the domestic market and other markets within Malawi that are at a similar distance as the domestic-foreign market pair. The findings show that export bans, in the short run, are associated with lower domestic prices, lower relative prices, and less seasonality in prices in Malawi. This is after accounting for harvest levels and the existence of trade restrictions in neighboring countries. The short-run effects of the export bans help explain why policymakers are likely to engage in the use of such policies. However, the welfare analysis shows that the welfare gains and poverty reduction effects are small in magnitude and likely to be offset by the long-run distortionary effects of restrictive trade policies.